Process Consultation in Improving the Effectiveness of Regional Police Competent Sub-Division Groups: A Qualitative Study - Alifia Ainun Rizky; Arsianita Nur Fattah (Business Research and Administration Innovation, 2026)
This study examines the effectiveness of the Competency Sub-Division (Subbagkompeten) group at the Human Resources Bureau (Ro SDM) of the X Regional Police using a qualitative approach with the group-level diagnostic model from Cummings and Worley (2015). The study aims to describe the dynamics of group effectiveness in terms of input, goal clarity, task structure, group composition, group functioning, and work norms, and to design appropriate interventions. Data were collected through semi-structured interviews with six participants (one sub-division head, one affairs officer, and four administrative non-commissioned officers), supported by observations, questionnaires, and document studies from September to December 2022. Data analysis was conducted using verbatim and stream analysis approaches. The results show that the overall effectiveness of the Sub-Division is in the high category, but there are significant problems in the group functioning component, particularly related to the lack of personal initiative in decision-making and dependence on external communication on a single personnel. These findings cause obstacles to achieving group output. Based on the diagnostic results, this study recommends process consultation intervention as an appropriate approach to improve communication, interpersonal relationships, and overall group effectiveness. This research provides a practical contribution to police organizations in managing human resources at the work group level